2013
DOI: 10.1021/om300487r
|View full text |Cite
|
Sign up to set email alerts
|

Bulky N-Phosphinomethyl-Functionalized N-Heterocyclic Carbene Chelate Ligands: Synthesis, Molecular Geometry, Electronic Structure, and Their Ruthenium Alkylidene Complexes

Abstract: A new, extremely bulky, and electron-rich N-phosphinomethyl-functionalized N-heterocyclic carbene ligand, 5a ( tBuNHCP tBu), and a somewhat less bulky congener, 5b (MesNHCP tBu), forming five-membered chelate rings with metal centers, have been synthesized in four steps starting from the easily accessible di-tert-butyl(hydroxymethyl)phosphine oxide (1). 5a was isolated and fully characterized by spectroscopic methods including UV-photoelectron spectroscopy and X-ray diffraction. The reaction of 5a with [Ru(COD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 96 publications
1
27
0
Order By: Relevance
“…Although a few phosphine-substituted NHCs were published at the time we started this work, [13] none of those ligands were applied as a polydentate gold ligand. Meanwhile, a few macrocyclic cationic gold complexes, [39][40][41] as well as Cu, Ag, Ru, Ni, Pd and Pt compounds with N-phosphorylated or N-phosphinomethyl-substituted NHCs, were reported by Braunstein, Kostyuk and Hofmann (Scheme 1), [42][43][44][45] but to the best of our knowledge, neutral gold complexes with phosphorus-containing NHCs are still unknown. Herein, we present a full account of phosphinoethyl-tethered NHC ligands in gold(I) chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Although a few phosphine-substituted NHCs were published at the time we started this work, [13] none of those ligands were applied as a polydentate gold ligand. Meanwhile, a few macrocyclic cationic gold complexes, [39][40][41] as well as Cu, Ag, Ru, Ni, Pd and Pt compounds with N-phosphorylated or N-phosphinomethyl-substituted NHCs, were reported by Braunstein, Kostyuk and Hofmann (Scheme 1), [42][43][44][45] but to the best of our knowledge, neutral gold complexes with phosphorus-containing NHCs are still unknown. Herein, we present a full account of phosphinoethyl-tethered NHC ligands in gold(I) chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…In the mechanism of the Dötz reaction, he found that chromacyclobutene structures were unrealistic intermediates and instead proposed vinylcarbene complexes as much more stable isomers [64,68,88]. Other research projects of his group included the synthesis of ruthenium–carbene complexes with cis -dichloro ligands for olefin metathesis catalysis [8687 9091 98100 108,132,138,147], the characterization of copper–carbene complexes as intermediates in the cyclopropanation of alkenes [102,106,113,119120], as well as detailed studies into the mechanism of the hydroformylation of alkenes. An improved understanding of this industrially important process was achieved by a combination of ligand design for the rhodium catalysts, kinetic studies, and high-level quantum-chemical calculations [126,135,142,145146 152,155].…”
Section: Peter Hofmann a Multifaceted Organometallic Chemistmentioning
confidence: 99%
“… 19 Progress has been severely hampered due to difficulties accessing azolium salt 5 , with the problematic reduction of 4 being achievable only with a large excess of trichlorosilane (27.0 equiv) in anhydrous degassed chlorobenzene at elevated temperature over 2 days. 19 As well as the lengthy reaction time, we experienced some reproducibility issues, with the unsuccessful reduction being accompanied by the decomposition of the precious azolinium 4 , previously obtained via a multistep synthesis. 19 In light of this, a simple procedure for the conversion of 4 to 5 would be a great advantage.…”
Section: Introductionmentioning
confidence: 99%
“… 19 As well as the lengthy reaction time, we experienced some reproducibility issues, with the unsuccessful reduction being accompanied by the decomposition of the precious azolinium 4 , previously obtained via a multistep synthesis. 19 In light of this, a simple procedure for the conversion of 4 to 5 would be a great advantage. Such a process might also permit access to other challenging phosphine(III) and metal catalysts as well as permitting the recovery of the valuable phosphine(III) ligands: “closing the phosphorus cycle” is of increasing importance due to environmental and availability concerns.…”
Section: Introductionmentioning
confidence: 99%